Distributed agency in HRI—an exploratory study of a narrative robot design - Graf, Philipp; Zarp-Falden, Christian Sønderskov; Naik, Lakshadeep; Lefeuvre, Kevin Bruno; Marchetti, Emanuela; Hornecker, Eva; Sørensen, Mads Bergholdt; Hemmingsen, Laurits Valberg; Just Christensen, Ebbe Vincent; Bodenhagen, Leon; Krüger, Norbert; Bischof, Andreas (Frontiers in Robotics and AI, 2024)
We explore an alternative approach to the design of robots that deviates from the common envisionment of having one unified agent. What if robots are depicted as an agentic ensemble where agency is distributed over different components? In the project presented here, we investigate the potential contributions of this approach to creating entertaining and joyful human-robot interaction (HRI), which also remains comprehensible to human observers. We built a service robot—which takes care of plants as a Plant-Watering Robot (PWR)—that appears as a small ship controlled by a robotic captain accompanied by kinetic elements. The goal of this narrative design, which utilizes a distributed agency approach, is to make the robot entertaining to watch and foster its acceptance. We discuss the robot’s design rationale and present observations from an exploratory study in two contrastive settings, on a university campus and in a care home for people with dementia, using a qualitative video-based approach for analysis. Our observations indicate that such a design has potential regarding the attraction, acceptance, and joyfulness it can evoke. We discuss aspects of this design approach regarding the field of elderly care, limitations of our study, and identify potential fields of use and further scopes for studies.